The Accuracy of Arrest Data in the National Incident-Based Reporting System (NIBRS) - Cross, Theodore P. (Crime & delinquency, 2023)
This study compared NIBRS arrest data in a statewide sample with arrest and summons data on the same cases collected directly from law enforcement agencies (LEAs). NIBRS matched LEA data in 84.1% of cases. However, 5.8% of LEA arrests and 52.9% of LEA summons were false negatives, that is, they were incorrectly represented as not cleared by arrest in NIBRS. False negatives were more likely when more than 1?day elapsed between incident and arrest and when the crimes were sexual assault or intimidation. False negatives were less likely in small LEAs (for summons) Recommendations are presented for improving accuracy.